Focal Seizures and Subependymal Nodules in a Patient with Tuberous Sclerosis Complex: A Case Report with a Positive Genetic Testing - Valbona Govori; Bujar Gjikolli; Elsa Berisha; Naim Zeka (International Journal of Biomedicine)
Tuberous sclerosis complex (TSC) is an autosomal dominant genetic disorder causing non-malignant tumors in various organs. This case report details a 5-month-old infant admitted for recurrent focal seizures characterized by rhythmic jerking of the left limbs and head deviation. Physical examination revealed hypopigmented macules, while brain MRI showed subependymal nodules and subcortical lesions. Cardiac rhabdomyomas were detected via echocardiography. Genetic testing confirmed a pathogenic TSC2 mutation. Despite the vigabatrin treatment, seizure control was partial. Long-term antiseizure therapy and follow-up remain essential for management. Further studies are needed to explore factors influencing therapeutic efficacy.